Pemberdayaan Kelompok Tani Oelamatan melalui Pelatihan Pembuatan Pakan Silase pada Ternak di Desa Salu, Kecamatan Miomafo Barat Kabupaten Timor Tengah Utara - Maria Selfiana Pasi; Marselinus Banu; Susanti Maria Yosefa Salu (Bakti Cendana, 2022)
Salu Village is one of the villages with a wide area and sufficient local forage resources are available as animal feed so that it is very suitable for livestock development. During the rainy season there is a lot of forage for livestock but it is not processed into preservative feed (silage) so that during the Kamarau season, the village of Salu lacks feed for livestock. An alternative to this problem is training in the manufacture of preservative feed (silage). The method used in community service activities is counseling accompanied by the practice of making preservative feed (silage) from forage kingres, lamtoro leaves and gamal leaves. Community service activities that have been carried out are the manufacture of preservative feed (silage). Service activities are carried out through counseling and practice (demonstrations of making silage feed) and the application of silage feed to cattle. From the observations, the people of Salu village look very enthusiastic because they want to move forward. Keywords: Feed, Forage, Silage